Process Evaluation of the NYU Caregiver Intervention-Adult Child. (4th May 2017) - Gaugler, Joseph E; Reese, Mark; Mittelman, Mary S
Abstract: Purpose of the Study: A noted limitation of dementia caregiver intervention research is a lack of focus on the mechanisms of successful programs. The purpose of this study was to conduct a process evaluation of the New York University Caregiver Intervention-Adult Child (NYUCI-AC) to describe its delivery and determine which of its components were associated with key outcomes (caregiver stress and well-being; care recipient residential care admission). Design and Methods: Adult child caregivers randomly assigned to receive the NYUCI-AC intervention ( n = 54) were included. Detailed data on the frequency and duration of each intervention component received, 4-month review checklists, and regular caregiver assessments were collected. Quantitative (descriptive, logistic regression, Cox proportional hazards models, growth curve models) and qualitative thematic analyses were performed. Results: Adult children receiving the NYUCI-AC completed a mean of 5.19 individual and family counseling sessions; it took on average a little over 11 months to do so. All NYUCI-AC counseling components were generally well-received and improved caregivers' management of care-related stress. The individual counseling sessions' clinical benefits in reducing primary subjective stress were most apparent in the first year of the intervention. Caregivers who experienced negative outcomes over time used more family sessions. Implications: A key mechanism of benefit for adult child caregivers in the NYUCI-AC was the frequent use of individual counseling sessions. The qualitative and quantitative results emphasize the value of the NYUCI-AC's flexibility in allowing adult child caregivers to choose the timing and use of specific intervention components.